Synthesis, spectroscopy, magnetic and redox behaviors of copper(II) complexes with tert-butylated salen type ligands bearing bis(4-aminophenyl)ethane and bis(4-aminophenyl)amide backbones - Kasumov, Veli T.; Yerli, Yusuf; Kutluay, Aysegul; Aslanoglu, Mehmet (Pergamon-Elsevier Science Ltd, 2013)
New salen type ligands, N,N'-bis(X-3-tert-butylsalicylidene)-4,4'-ethylenedianiline [(X = H (1), 5-tert-butyl (2)] and N,N'-bis(X-3-tert-butylsalicylidene)-4,4'-amidedianiline [X = H (3), 5-tert (4)] and their copper(II) complexes 5-8, have been synthesized. Their spectroscopic (IR, H-1 NMR, UV/vis, ESR) properties, as well as magnetic and redox-reactivity behavior are reported. IR spectra of 7 and 8 indicate the coordination of amide oxygen atoms of 3 and 4 ligands to Cu(II). The solid state ESR spectra of 5-8 exhibits less informative exchange narrowed isotropic or anisotropic signals with weak unresolved low field patterns. The magnetic moments of 5 (2.92 mu(B) per Cu-II) and 6(2.79 mu(B) per Cu-II) are unusual for copper(II) complexes and considerably higher than those for complexes 7 and 8. Cryogenic measurements (300-10 K) show weak antiferromagnetic exchange interactions between the copper(II) centers in complexes 6 and 8. The results of electrochemical and chemical redox-reactivity studies are discussed. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: ESR; Optical spectroscopy; Magnetic properties; Chemical oxidation; Electrochemistry